Influence of Cell Type in In Vitro Induced Reprogramming in Cattle - Kaiana Recchia; Laís Vicari de Figueiredo Pessôa; Naira Caroline Godoy Pieri; Pedro Ratto Lisboa Pires; Fabiana Fernandes Bressan (Life, 2022)
Induced pluripotent stem cells (iPSCs) have been considered an essential tool in stem cell research due to their potential to develop new therapies and technologies and answer essential questions about mammalian early development. An important step in generating iPSCs is selecting their precursor cell type, influencing the reprogramming efficiency and maintenance in culture. In this study, we aim to characterize bovine mesenchymal cells from adipose tissue (bAdMSCs) and fetal fibroblasts (bFFs) and to compare the reprogramming efficiency of these cells when induced to pluripotency. The cells were characterized by immunostaining (CD90, SSEA1, SSEA3, and SSEA4), induced differentiation in vitro, proliferation rates, and were subjected to cell reprogramming using the murine OSKM transcription factors. The bFFs presented morphological changes resembling pluripotent cells after reprogramming and culture with different supplementation, and putative iPSCs were characterized by immunostaining (OCT4, SOX2, NANOG, and AP). In the present study, we demonstrated that cell line origin and cellular proliferation rate are determining factors for reprogramming cells into pluripotency. The generation of biPSCs is a valuable tool to improve both translational medicine and animal production and to study the different supplements required to maintain the pluripotency of bovine cells in vitro.